Research and development of an information system database security model (Journal of Mathematics Mechanics and Computer Science, 2019)
the article describes the methods of protecting the database and the information stored in it. The analysis of cyberattacks on information systems is presented. Some companies that provide services to protect information stored in databases, as well as structured and unstructured data, are considered. The developed database protection model is described, which displays the sequence of the encryption and decryption method. An algorithm of information encryption / decryption methods has been developed, which is based on the use of Base64 cryptographic encryption method. A fixed prefix is ​​described. The Base64 transcoding result for each ASCII-readable character and digit is presented. Briefly described inflation prefix. A software implementation of the described algorithm was implemented, developed for the Windows operating system in the Embarcadero RAD Studio development environment in the Deplhi programming language, using integration with other programming languages ​​and connected system libraries. A detailed description of the user instructions for the algorithm in question is given. The analysis of the software implementation of the proposed algorithm is carried out.
Keywords: protection of the database; information security; data security; protection model; application; database; enciphering; decoding